2020
DOI: 10.1136/rmdopen-2020-001424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Heel Enthesitis MRI Scoring System (HEMRIS) with clinical enthesitis and local metabolic activity on PET-CT

Abstract: ObjectiveTo compare the Heel Enthesitis MRI Scoring model (HEMRIS) with clinical and PET/CT outcomes in patients with cutaneous psoriasis (Pso), psoriatic arthritis (PsA) or ankylosing spondylitis (AS).MethodsThis prospective, observational study included 38 patients with Pso, PsA and AS. Patients were included regardless of presence or absence of clinical heel enthesitis. MRI-scans of both ankles and a whole-body 18F-FDG PET/CT were acquired. MRIs were assessed for enthesitis by two independent and blinded ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The patients with intractable hiccups after stroke undergo a CT scan; then an unsupervised multilayer image threshold segmentation algorithm with the combined effect of two-dimensional (2D) K-L divergence and MPSO was proposed to perform the multiple segmentation of CT images. The clinical efficacy of anisodamine combined with chlorpromazine had been investigated by injecting it at bilateral Neiguan acupoint in patients [ 23 , 24 ]. The intelligent algorithm was introduced into CT imaging to enhance the clarity of images, which was conducive to the diagnosis of patients' diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The patients with intractable hiccups after stroke undergo a CT scan; then an unsupervised multilayer image threshold segmentation algorithm with the combined effect of two-dimensional (2D) K-L divergence and MPSO was proposed to perform the multiple segmentation of CT images. The clinical efficacy of anisodamine combined with chlorpromazine had been investigated by injecting it at bilateral Neiguan acupoint in patients [ 23 , 24 ]. The intelligent algorithm was introduced into CT imaging to enhance the clarity of images, which was conducive to the diagnosis of patients' diseases.…”
Section: Introductionmentioning
confidence: 99%
“…By using the heel as the prototype, the OMERACT MRI group put forward the Heel Enthesitis MRI Scoring System (HEMRIS), which categorized the pathologies of enthesitis on MRI into inflammatory lesions and structural lesions ( Table 6 ) ( 78 , 79 ). This scoring system has been validated in patients with enthesitis at the Achilles tendon and plantar fascia and proved to be reliable ( 80 ). The inflammatory parameters evaluated intra-tendon hypersignal on T2w/short-tau inversion recovery (STIR) sequences, peri-tendon hypersignal, bone marrow edema, and bursitis, whereas structural lesions were defined as enthesophyte, bone erosion, and tendon thickening.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…It was hypothesized that, because the regional accumulation of 18F-FDG could reflect certain extent of tissue inflammation status, PET/CT could potentially be a promising tool in diagnosing enthesitis ( 80 ). However, studies showed that enthesitis as observed on MRI images was not correlated with the accumulation of 18F-FDG ( 80 ). Only the structural damage of the Achilles tendon was weakly correlated with the metabolic activity on PET/CT.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…72 Finally, a recent study confirmed the superiority of MRI, using the Heel Enthesitis MRI Scoring (HEMRIS) score, in detecting subclinical lesions is spondyloarthropathies (AS and PsA), at the level of Achilles tendon and plantar fascia: again FDG uptake was subtle or moderate. 73 Relatively little has been described in psoriatic arthritis, often in series combining other types of spondylarthritis. The important issue with this disorder is the peculiar distribution with asymmetric distribution and oligoarticular FDG uptake in hands and feet with row or ray distribution.…”
Section: Spondyloarthropathies and Other Rheumatic Disordersmentioning
confidence: 99%